Aplikasi Vermikompos dalam Meningkatkan Pertumbuhan dan Hasil Melon (Cucumis melo L.) - Budiyati Ichwan; Hajar Setiaji; Y.G Armando; Eliyanti Eliyanti; Zulkarnain Zulkarnain; Lily Ayuandriani (Jurnal Media Pertanian, 2022)
This study aimed to examine the effect of vermicompost in increasing melon growth and yield and to obtain a dose of vermicompost that was able to provide the best melon growth and yield. The research design used was a Randomized Block Design (RBD) with one factor, namely the dose of vermicompost consisting of: 0 tonha-1; 5 tonha-1; 15 tonha-1; 25 tonha-1; and 35 tonha-1. The results showed that the application of vermicompost increased plant length, number of leaves, leaf area, stem diameter, fruit diameter, and weight per fruit of melon plants. The dose of vermicompost that gave the best melon growth and yield was 25 tonha-1, with a weight per fruit of 1,8 kg, and productivity of 50 tonha-1, 1,2 times greater than the potential yield of melon